[PP.23.10] CLINICAL IMPACT OF ANGIOTENSIN CONVERTING ENZYME (ACE) POLYMORPHISM ON DEVELOPMENT OF CARDIOVASCULAR AND METABOLIC COMPLICATIONS IN SUBJECTS WITH RESISTANT HYPERTENSION. (September 2016) - Quartuccio, S.; Mandraffino, G.; Di Stefano, R.; Trapani, G.; Felice, F.; Lizio, G.; Saitta, A.; Imbalzano, E.
Abstract : Objective: The renin-angiotensin system and endothelial function have been both associated with hypertension, but there are very few data in resistant hypertension. The aim of the present study was to assess the relationship between insertion/deletion polymorphism in the gene encoding the angiotensin-converting enzyme (ACE I/D) and estimation of cardiovascular and metabolic complications in resistant hypertensive patients. Design and method: In the present study we analyzed and genotyped data from 150 patients with resistant hypertension. We have evaluated arterial stiffness (AS) indices, carotid intima-media thickness (cIMT), HOMA index and clinical data. Results: D allele was more prevalent, and 74 patients presented DD homozygosis. Sixty-eight patients had metabolic syndrome (MetS), without significant differences between DD and I allele carriers. DD genotype appeared strongly associated with higher HOMA values (p < 0.001), and also with both AIx (p = 0.003) and PWV (p = 0.023). A significant association was found between DD genotype and cIMT (p < 0.005), and the presence of carotid plaques (p < 0.001). HOMA was correlated with AS (PWV: p < 0.001; AIx: p < 0.01). Conclusions: Our results are in agreement with experimental evidences suggesting that DD genotype appeared to be associated with AS, increased cIMT, HOMA index, and the presence of carotid plaques, and confirming that D allele plays an important risk role on development of cardiovascular and metabolic complications in patients with resistant hypertension, independently from the presence of other risk factors.